(untitled) (Al-Academy, 2024)
Experimentation Multi effective and fertile grew human desire to discover new ways to express beauty in artwork .And dabble term experimentation in the performing arts and arts architecture, cinema and television in the test forms and interest in the visual effects and movements seek to establish and beauty and schools of thought in literature and art. This study aims to identify